Social Competence of Arabic Language Teachers Based on the National Education Standards - Isop Syafei; Dadan Nugraha (Gunung Djati Conference Series, 2025)
This study aims to identify the social competence of Arabic language teachers based on the indicators of the National Education Standards (SNP). A descriptive qualitative approach was employed to portray the social competence of Arabic language teachers according to the SNP indicators. Primary data were obtained through interviews, observations, and documentation, while secondary data were gathered from official documents. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and inductive conclusion drawing to produce valid findings. The results indicate that the social competence of Arabic language teachers within the SNP framework includes the ability to communicate effectively, empathetically, and politely; to socialize within the school and the community; to respect diversity; to adapt to local culture; and to integrate Islamic values. Such competence is essential for conveying Arab-Islamic cultural values in the Indonesian context, ensuring that learning not only teaches the language but also fosters character building, tolerance, and harmonious social relations in educational and community settings. These findings suggest that Arabic language teachers should engage in continuous professional development focusing on effective communication, cross-cultural understanding, and the integration of Islamic values. Schools are encouraged to support community-based collaborative programs to strengthen teachers’ roles in fostering character, tolerance, and harmonious social relations in alignment with Indonesia’s cultural context.